2010
DOI: 10.1152/ajplung.00190.2009
|View full text |Cite
|
Sign up to set email alerts
|

Functional importance of the NH2-terminal insertion sequence of lung surfactant protein B

Abstract: Lung surfactant protein B (SP-B) is required for proper surface activity of pulmonary surfactant. In model lung surfactant lipid systems composed of saturated and unsaturated lipids, the unsaturated lipids are removed from the film at high compression. It is thought that SP-B helps anchor these lipids closely to the monolayer in three-dimensional cylindrical structures termed "nanosilos" seen by atomic force microscopy imaging of deposited monolayers at high surface pressures. Here we explore the role of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 74 publications
1
33
1
Order By: Relevance
“…KL4 is loosely based on the C-terminal sequence of SP-B (i.e., SP-B residues 63–78 or MB/S-MB residues 26–41 [19]), and shows surfactant activity when folded as an α-helix (see Figure 4C). Several mechanisms have been proposed to account for the surfactant activities of KL4, ranging from an ‘SP-B-like’ model [58,84] to one similar to that of the transmembrane helical surfactant protein C (SP-C) [85,86] (see Figure 4D), but none has yet gained general acceptance. SP-C is a short 35-residue hydrophobic protein in human lungs with a relatively unstructured N-terminus (residues 1–8) with residues 9 to 34 forming a stable α-helix in the mid- and C-terminal regions (PDB: 1SPF).…”
Section: Mini-b (Mb) and Super Mini-b (S-mb) Synthetic Peptidesmentioning
confidence: 99%
“…KL4 is loosely based on the C-terminal sequence of SP-B (i.e., SP-B residues 63–78 or MB/S-MB residues 26–41 [19]), and shows surfactant activity when folded as an α-helix (see Figure 4C). Several mechanisms have been proposed to account for the surfactant activities of KL4, ranging from an ‘SP-B-like’ model [58,84] to one similar to that of the transmembrane helical surfactant protein C (SP-C) [85,86] (see Figure 4D), but none has yet gained general acceptance. SP-C is a short 35-residue hydrophobic protein in human lungs with a relatively unstructured N-terminus (residues 1–8) with residues 9 to 34 forming a stable α-helix in the mid- and C-terminal regions (PDB: 1SPF).…”
Section: Mini-b (Mb) and Super Mini-b (S-mb) Synthetic Peptidesmentioning
confidence: 99%
“…This suggests that interactions, between SP-B components and lipids in some mixtures, can compete with the interactions responsible for flattening bilayers in mechanically oriented samples, thereby promoting departures from planar geometry over large length scales. Proper functioning, and maintenance, of lung surfactant requires the recruitment of surfactant material into the surface-active layer from adjacent bilayer reservoirs, and the transfer of material to such reservoirs as lung volume varies (Zuo et al 2008; Rugonyi et al 2008; Possmayer et al 2010; Frey et al 2010). This implies a need for close contacts between bilayers and surface layers.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the surface-active layer is also thought to require that material squeezed out of the monolayer during compression remain anchored to the monolayer and available for recruitment back into the monolayer during expansion. The N-terminal region of SP-B has been implicated in the stabilization of so-called nanosilo reservoirs (Frey et al 2010), and the formation of such structures presumably involves highly curved intermediate states. Accordingly, a propensity for SP-B and its fragments to compete with the orienting influence of a proximal flat surface, such as in a mechanically oriented bilayer sample, might be relevant to surfactant function.…”
Section: Introductionmentioning
confidence: 99%
“…The region of SP-B's N-terminus preceding the first helix, termed the “insertion sequence” [41], [42], is of particular interest. The segment of SP-B comprising residues 1–7, Phe-Pro-Ile-Pro-Leu-Pro-Tyr, resembles proline-rich cell-penetrating peptides [43].…”
Section: Introductionmentioning
confidence: 99%
“…The functional role of the insertion sequence has been probed in the context of N-terminal peptides of SP-B and it was found that mutation of any of the proline residues led to decreased surface activity [44]. More recently, the insertion sequence has been examined by adding it on to Mini-B, to create a construct of SP-B, termed “Super Mini-B” (SP-B (1–25,63–78)), which retains the N-terminal insertion sequence, two of the four SP-B helices, specifically the N-terminal helix and the C-terminal helix, the two disulfide bonds that help link the helices together, and an overall charge of +7 [41], [42]. The 7 insertion sequence residues, along with the tryptophan at position 9, were proposed to stabilize the formation of “nanosilos”, structures seen by atomic force microscopy imaging of monolayers deposited at high surface pressures [41].…”
Section: Introductionmentioning
confidence: 99%